HUBUNGAN ANTARA TINGKAT PENGETAHUAN DENGAN POLA MAKAN PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS KARTASURA - Sari, Mellyana Purnama; Fahrun Nur Rosyid (Jurnal Keperawatan Malang, 2024)
Background: The correct diet, blood glucose management, and quality of life are all impacted by patients' levels of knowledge on diabetes and nutrition. consequences from Type 2 Diabetes Mellitus (T2DM), which is often associated with a poor diet, can have a significant impact on patients' quality of life. These consequences can include damage to the kidneys, blood vessels, and neurological system. To maintain blood sugar levels and avoid difficulties, proper management is crucial, which includes a high degree of education and a healthy diet.Purpose: to determine the relationship between the level of knowledge and eating patterns in patients with type 2 diabetes mellitus at the Kartasura Community Health Center.Methods: The research in question is a cross-sectional quantitative observational study. In this study, 174 participants with type 2 diabetes mellitus were chosen at random using an incidental selection strategy, which is a non-probability sampling method. A questionnaire was used to gather data, which assessed the respondents' dietary habits and their degree of diabetes awareness. The association between the two variables was determined by data analysis utilizing the Spearman correlation testResult: The correlation results obtained a significant value of the level of knowledge with diet patterns with a P-value of 0.000 <0.05, and most respondents had a low level of knowledge as many as 66 respondents (37.9%) and were not compliant with the diet program being undertaken as many as 112 (64.4%) respondentsImplication: The study's findings show that patients with diabetes mellitus at the Kartasura Health Center's knowledge level is correlated with their eating habits. It is believed that this discovery will help enhance the understanding of type 2 diabetes mellitus and make it easier for people with this disease to stick to their diet plan